Assessment of mental health disorders in individuals with chronic diseases during the COVID-19 pandemic - Danijela Radulović; Srdjan Mašić; Dejan Bokonjić; Svetlana Radević; Ivana Simić Vukomanović; Biljana Mijović; Maja Vuković; Milena Dubravac Tanasković; Mirka Jojić; Jelena Vladičić Mašić; Dragan Spaić (Биомедицинска истраживања, 2024)
Introduction: The COVID-19 pandemic has had a significant impact on the mental health of individuals with chronic diseases. Contributing factors include limited access to healthcare during lockdowns, fear of infection, and heightened stress due to poorer outcomes of COVID-19 infection in this population. The aim of this study was to examine the presence of depression, anxiety, and stress in the second year of the COVID-19 pandemic among individuals with pre-ex isting cardiovascular, malignant, chronic respiratory diseases, or diabetes mellitus. Methods: A cross-sectional study was conducted among the general population of the eastern region of Republic of Srpska during December 2021 and January 2022. Depression, anxiety, and stress were assessed using the DASS-21 scale, while data on comorbidities were collected through a questionnaire from an epidemiological population-genetic study conducted concurrently. Results: A total of 1,372 participants from the eastern region of Republic of Srpska were included in the study, consisting of 40.0% males and 60.0% females. Participants were aged 20 years and older, with an average age of 50.6 years. The study found that depression, anxiety, and stress were statistically significantly more prevalent among participants with pre-existing cardiovascular or chronic respiratory diseases compared to those without such conditions. Additionally, participants with a history of malignant diseases or diabetes mellitus were significantly more depressed and anxious than those without these conditions. Conclusion: The findings of this study may contribute to the development of policies aimed at improving mental health and preventing mental disorders in individuals with comorbidities.
Keywords: mental health; chronic diseases; COVID-19 pandemic